Humor gráfico y comprensión de deseos (2012)
This paper aims to document the understanding of desires from two approaches, one is graphic humor and the other is preferences with children between two years eight months and three years. Methodologically, we work with the microgenetic method combined with a time-series study over 10 sessions for two months. Two types of analysis are used, an intra-group and through an intra-subject one; the latter captures the various ways which children go when faced with tasks. The results identify three trends in performance: stable trend, downward trend, and upward trend. They also show the importance of working on other ways for the study of cognitive processes in terms of methodology and these results confirm graphic humor as an alternative for the study of mental states.